Biosynthesis in vitro of immunoreactive 31,000-dalton corticotropin/β-endorphin-like material by bovine hypothalamus - Liotta, Anthony S. (1979)
Enzymatically dispersed bovine hypothalamic or cortical tissue was maintained in culture in the presence of (3)H-labeled amino acids. After such incubation, extracts of cells and of media contained (3)H-labeled products that were specifically bound by immobilized affinity-purified antisera to corticotropin (ACTH) and β-endorphin. The majority of these products eluted in the void volume (V(0)) upon Sephadex G-50 gel filtration; minor (3)H-labeled products eluted in the regions of the ovine β-lipotropin marker and in fractions having apparent molecular weights of approximately 12,000 and 3800. Sequential use of these immobilized antisera revealed that most of the V(0) material contained both ACTH and β-endorphin antigenic determinants within the same molecule(s), whereas retarded material contained only one of the determinants. When this V(0) material was rerun on a Sephadex G-75 column, it coeluted with the 31-kilodalton precursor of both ACTH and β-endorphin obtained from a bovine anterior pituitary extract. Thus, the high molecular weight immunoreactive ACTH/β-endorphin-like (3)H-labeled product(s) derived from the hypothalamic culture is similar to the pituitary-derived precursor in containing the dual antigenic determinants and in its gel filtration characteristics. In contrast, the cortex-derived cell preparation was devoid of (3)H-labeled products specifically reactive with the antisera employed.